Case report: Persistent Müllerian duct syndrome and enlarged prostatic utricle in a male dog - Welsh, Peter J.; McDaniel, Kaylyn; Goldsmith, Elizabeth W.; Ramsay, Joshua D.; Conley, Alan; Owen, Tina Jo; Ambrosini, Yoko M.; Ciccarelli, Michela (Frontiers in Veterinary Science, 2023)
A 1-year-old male intact Miniature Schnauzer mix was presented for chronic intermittent hematuria. Abdominal ultrasonography revealed a large, fluid-filled cystic structure extending cranially and dorsally to the prostate. Computed tomography scan images revealed that the fluid-filled cavity resembled a uterus, with both horns entering the scrotum through the inguinal canal adjacent to the testes. On cytogenetic analysis, the dog was found to have a homozygote mutation on AMHRII consistent with persistent Müllerian duct syndrome (PMDS). A gonadohysterectomy was performed, and surgical and histologic findings confirmed the presence of a uterus, oviducts, vagina, and testes in this dog. Additionally, an intraoperative fluoroscopy exam revealed a communication between the uterus and the bladder via an enlarged utricle, explaining the hematuria and urine in the reproductive tract (urometra). To our knowledge, this is the first clinical report of a phenotypically intact male dog with PMDS and urometra due to an enlarged prostatic utricle. This case illustrates a combination of a disorder of sex and urogenital sinus development.